1994
DOI: 10.1080/02786829408959721
|View full text |Cite
|
Sign up to set email alerts
|

Motor Vehicle Contributions to Fine Carbonaceous Aerosol in Los Angeles

Abstract: The contributions to the fine ( d , < 3.5 pm) carbona-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In the urban environment, motor vehicle emissions are often the main anthropogenic source of air pollution, significantly contributing to the deterioration of urban air quality (5,6). Most of the research for motor vehicle particulate emissions has focused on mass concentrations in the exhaust, either as total mass concentration (7), or PM10 (mass concentration of particles smaller than 10 µm). The mass of submicrometer particles is often insignificant in comparison with the total mass of emitted particles due to the fact that a small number of large particles contribute most of the mass; submicrometer number concentrations can change by orders of magnitude without consequent changes in the total mass concentration measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In the urban environment, motor vehicle emissions are often the main anthropogenic source of air pollution, significantly contributing to the deterioration of urban air quality (5,6). Most of the research for motor vehicle particulate emissions has focused on mass concentrations in the exhaust, either as total mass concentration (7), or PM10 (mass concentration of particles smaller than 10 µm). The mass of submicrometer particles is often insignificant in comparison with the total mass of emitted particles due to the fact that a small number of large particles contribute most of the mass; submicrometer number concentrations can change by orders of magnitude without consequent changes in the total mass concentration measurements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the EGA profiles did provide a clear means of distinguishing black from organic carbon. Using carbon monoxide as a tracer, Pratsinis (1994) allocated 70% of the black carbon at Duarte for 1987-1988 to motor vehicle sources, or sources with the same black-carbon-to-carbon-monoxide ratio. For the same time period and general location, Kaplan and Gordon (1994) found that 30% of the black carbon was modern.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…These results are consistent, and they indicate the importance of primary emissions from nonfossil sources. Pratsinis (1994) compared organic carbon/black carbon (OC/BC) ratios for ambient aerosols with those from primary motor vehicle emissions as measured in an automotive tunnel. Not surprisingly, he found that OC/BC ratios for ambient aerosol varied but at all times were at least as high as those from the tunnel.…”
Section: Source Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The BC particles are generally very hydrophobic but it is converted as hydrophilic because of physical and/or chemical changes occurring during atmospheric aging process (Weingartner et al, 1997;Bauer et al, 2010). The BC aerosols have been well studied in terms of their lifetime, concentration, sources and optical properties on a fixed wavelength (Ogren and Charlson, 1983;Hildemann et al, 1994;Pratsinis, 1994;Hansen et al, 1993;Köhler et al, 2001;Streets et al, 2001). The optical properties of mineral dust externally and internally mixed with BC have been modeled by many scientists (Fuller et al, 1999;Bond and Bergstrom, 2006;Lesins et al, 2002;Jacobson, 2000).…”
Section: Introductionmentioning
confidence: 99%